DEVELOPING CRITICAL CONSCIOUSNESS: A CRITICAL LITERACY APPROACH TO ANALYZING MEDIA REPRESENTATIONS OF IMMIGRANTS IN A HIGH SCHOOL ENGLISH CLASS - Yusuf Yusuf; Samantha Gonzales; Sarah Williams (Lingeduca: Journal of Language and Education Studies, 2025)
The portrayal of immigrants in media significantly shapes public perceptions, often reinforcing stereotypes and societal biases. Despite the growing importance of media literacy, high school curricula often overlook critical engagement with such representations. This study explores the application of a critical literacy approach in a high school English classroom to analyze media portrayals of immigrants. The primary objective was to enhance students' critical consciousness by equipping them with tools to deconstruct media messages, specifically focusing on immigrant representations. A qualitative research design was employed, utilizing pre- and post-surveys, classroom observations, and student interviews to assess the impact of the intervention. The results revealed a notable increase in students' ability to identify stereotypes and biases in media content, with 85% of students demonstrating heightened awareness of media's role in shaping public attitudes toward immigrants. Students reported greater confidence in critiquing media portrayals, reflecting a deeper understanding of the power dynamics involved. The findings suggest that a critical literacy approach fosters critical thinking skills and social awareness, empowering students to actively engage with media. This study underscores the potential of integrating critical literacy practices into high school curricula to address social justice issues. Future research should explore the long-term effects of such interventions in diverse educational contexts.